Adverse effects of statin therapy: perception vs. the evidence - focus on glucose homeostasis, cognitive, renal and hepatic function, haemorrhagic stroke and cataract - Mach, François; März, Winfried (European heart journal, 2018)
AbstractAims. To objectively appraise evidence for possible adverse effects of long-term statin therapy on glucose homeostasis, cognitive, renal and hepatic fu
Published: 27 April 2018
Gesehen am 07.08.2019